Brand credibility, perceived quality and perceived value: a study of customer satisfaction - Othman, Manisah; Kamarohim, Nor Azlina; Mohd Nizam, Fadilah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This research examines the relationship of brand credibility, perceived quality and perceived value towards customer satisfaction and to what extent customer satisfaction influences brand loyalty. A questionnaire survey method was used to collect data for this study and 100 footwear consumers from shopping malls located in the Klang Valley, Malaysia participated in this study. This study to determine the influence of these factors on customer satisfaction and brand loyalty. The research findings show that there is positive influence of brand credibility, perceived quality and perceived value on customer satisfaction.